ELECTRON BEAM IRRADIATION OF C60(OH)10 - Janjua, S. A.; Robinson, A. (The Nucleus, 2010)
The polyhydroxylated fullerene derivative, or fullerol, C60(OH)10, has been investigated as an electron beam resist. Films of fullerol of âˆ¼ 200 nm thickness, were prepared on silicon substrates using spin coating. Upon exposure with electrons at 20 keV the fullerol displayed negative tone resist behaviour after development with isopropyl alcohol:cyclohexanone (1 : 4). The fullerol became insoluble after exposure to a dose of âˆ¼ 10 mC/cm2 for 20 keV electrons.